2008
DOI: 10.1158/1078-0432.ccr-08-0476
|View full text |Cite
|
Sign up to set email alerts
|

Derlin-1 Is Overexpressed on the Tumor Cell Surface and Enables Antibody-Mediated Tumor Targeting Therapy

Abstract: Purpose: Tumor targeting therapy is one of the most promising strategies for anticancer treatment. Derlin-1has been reported to participate in misfolded protein dislocation and integrates into the endoplasmic reticulum (ER) membrane to survey for such protein aggregates. We elucidate herein that Derlin-1can leak to the plasmalemma from the ER in tumor cells and may have clinical application as a novel cancer target in the hope of developing a new tumor targeting therapy. Experimental Design: The cell surface e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 33 publications
5
25
0
Order By: Relevance
“…12 Although there is no precedent study on the expression of Derlin proteins in CLL cells ( Figure 2B,D), Derlin-1 is overexpressed in many solid malignancies and is a potential molecular target for therapeutic intervention. 37 Our results now suggest that the IRE-1/ XBP-1 pathway is a promising target for CLL treatment ( TCL1 drives malignant progression of CLL via dysregulated expression of transcription factors and AID ( Figure 3B). IRF4 alone can transform cells in vitro.…”
Section: Tcl1 Activates the Er Stress Response In Cll 1035mentioning
confidence: 71%
“…12 Although there is no precedent study on the expression of Derlin proteins in CLL cells ( Figure 2B,D), Derlin-1 is overexpressed in many solid malignancies and is a potential molecular target for therapeutic intervention. 37 Our results now suggest that the IRE-1/ XBP-1 pathway is a promising target for CLL treatment ( TCL1 drives malignant progression of CLL via dysregulated expression of transcription factors and AID ( Figure 3B). IRF4 alone can transform cells in vitro.…”
Section: Tcl1 Activates the Er Stress Response In Cll 1035mentioning
confidence: 71%
“…We identified DERL1 as a direct downstream target gene of miR-598 using bioinformatics method that was further confirmed by the luciferase reporter assay. DERL1 is overexpressed in NSCLC; it also promotes cancer cell invasion via EGFR-ERK-mediated upregulation of MMP-2 and MMP-9 [16, 19, 21]. However, the correlation between DERL1 and miR-598 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The family of Der1 proteins has emerged as a vital component of the ERAD pathway [15]. DERL1 is a partner of the p97 ATPase complex and plays a key role in the mislocalization of the misfolded protein; it also integrates into the endoplasmic reticulum (ER) membrane to survey such protein aggregates [16, 17]. Recently, several studies have demonstrated that DERL1 contributes to carcinogenesis and tumor progression, and the upregulation of DERL1 expression promotes the development of colon cancer, esophageal cancer, and bladder cancer [18-20].…”
Section: Introductionmentioning
confidence: 99%
“…Derlin-1, a partner of the p97 ATPase complex, was initially reported to mediate the elimination of misfolded proteins from the endoplasmic reticulum (ER) and retrotranslocation of proteins into the cytosol [3][4][5]. Accumulating evidence has strongly implicated that Derlin-1 plays an important and multifaceted role in cancer progression [6][7][8][9][10][11][12]. Derlin-1 was confirmed to promote hepatocellular carcinoma endothelial cell survival and growth [13].…”
Section: Introductionmentioning
confidence: 99%